Quaternary precursor of sodium-ion battery as well as preparation method and application of quaternary precursor
The "core-shell" structure quaternary precursor for sodium ion batteries is prepared by a two-stage method, which solves the problems of uneven distribution and segregation of elements in the co-precipitation process and achieves the preparation of precursors with high density and good morphology.
Patent Information
- Application Number
- CN202411419629.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-12
AI Technical Summary
When the prior art dopant of multiple metal elements in the co-precipitation process, it is easy to cause uneven element distribution, and some metal elements are prone to segregation during the co-precipitation process, resulting in low tap density and poor morphology of the precursor.
A two-stage method is used to prepare a "core-shell" structure quaternary sodium ion battery precursor. By adjusting the pH value of the reaction system in stages, the core is first formed, and then the doping metal is coated under appropriate pH conditions to control the doping. Deposition rate of metal to avoid element segregation.
Achieved the preparation of sodium-ion battery quaternary precursors with dense structure, high tap density and good morphology. The product has good consistency, simple operation and strong applicability.
Smart Images

Figure CN119330424A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion battery related materials and relates to a preparation process of a precursor, and specifically relates to a sodium ion battery quaternary precursor and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries are secondary batteries that have the same working principle and similar battery components as lithium-ion batteries. In the face of a shortage of lithium resources, sodium-ion batteries have attracted much attention due to their abundant sodium resources, low cost, and good overall performance. They have good application prospects in energy storage and power batteries.
[0003] The positive electrode materials of sodium-ion batteries can be divided into layered oxide type, polyanion type and Prussian blue type, among which layered oxide is the most widely used. The structural composition of the precursor has a huge influence on the performance of layered oxide, which in turn affects the electrochemical performance of sodium-ion batteries.
[0004] When studying the systems suitable for transition metals in layered oxides, it was found that appropriately doping different elements in the nickel-iron-manganese-based sodium-ion battery precursor can improve the rate performance and cycle performance of the sodium-ion battery. For example, doping with Cu can improve the air stability, cycle stability and rate performance of the material; doping with Zn can provide vacancies for the embedding of sodium ions, thereby ensuring the rate performance of the material.
[0005] In the prior art, other elements are usually doped into the precursor through a co-precipitation process. However, the simultaneous co-precipitation of multiple metal elements can easily lead to uneven element distribution, and some metal elements are prone to segregation during the co-precipitation process, resulting in a low tap density and poor morphology of the precursor. Summary of the invention
[0006] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a sodium ion battery quaternary precursor; in the second aspect, the present invention provides a method for preparing a sodium ion battery quaternary precursor; in the third aspect, the present invention provides a positive electrode material; in the fourth aspect, the present invention provides a battery.
[0007] In a first aspect, the present invention provides a sodium ion battery quaternary precursor, comprising a core and a shell layer covering at least a portion of the surface of the core; the chemical formula of the core is Ni x1 Zn y1 Fe z1 Mn 1-x1-y1-z1 (OH)2, wherein 0.1≤x1≤0.4, 0≤y1≤0.03, 0.1≤z1≤0.5, x1+y1+z1<1; the chemical formula of the shell is Ni x2 Zn y2 Fe z2 Mn1-x2-y21-z2 (OH)2, wherein 0.1≤x2≤0.4, 0.04≤y2≤0.12, 0.1≤z2≤0.5, x2+y2+z2<1; the tap density of the sodium ion battery quaternary precursor is 1.4~1.8g / cm 3 .
[0008] Preferably, the primary particles of the sodium ion battery quaternary precursor are in the form of ordered intercalated sheets; and the secondary particles of the sodium ion battery quaternary precursor are in the form of spheres or quasi-spheres.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned sodium ion battery quaternary precursor, comprising the following steps: Step 1, mixing nickel salt, iron salt, manganese salt, zinc salt and a first antioxidant solution to obtain a metal salt mixed solution A; mixing nickel salt, iron salt, manganese salt, zinc salt and a first antioxidant solution to obtain a metal salt mixed solution B; wherein the zinc salt concentration in the metal salt mixed solution B is higher than the zinc salt concentration in solution A; Step 2, continuously introducing metal salt mixed solution A, precipitant solution and complexing agent solution into the bottom liquid of the reaction kettle under an inert atmosphere to prepare the core, wherein the preparation of the core includes a first stage and a second stage, and the pH value in the reaction system in the first stage is 0.5-1.0 higher than the pH value in the reaction system in the second stage; in the first stage, the pH value of the reaction system is adjusted to 11.0-12.0, and after a certain reaction time, the second stage is entered, and then the pH value of the reaction system is adjusted to 10.5-11.0, and the reaction time is a certain time; Step 3, stop introducing the metal salt mixed solution A, continue to introduce the metal salt mixed solution B, the precipitant solution and the complexing agent solution into the bottom liquid of the reactor, adjust the pH value of the reaction system to 9-10, react for a certain time, and obtain a slurry; Step 4, solid-liquid separation of the slurry obtained in step 3, and then solid-liquid separation, washing, and drying to obtain the sodium ion battery quaternary precursor material.
[0010] Preferably, the nickel salt, iron salt, manganese salt and zinc salt are each independently any one or more of sulfate, nitrate, acetate and chlorate.
[0011] Preferably, the precipitant solution is any one or more of a sodium hydroxide solution and a potassium hydroxide solution; more preferably, the precipitant solution is a sodium hydroxide solution.
[0012] Preferably, the concentration of the precipitant solution is 8-12 mol / L.
[0013] Preferably, the complexing agent solution is any one or more of sodium citrate solution, sodium fluoride solution, hydroxyethylethylenediaminetriacetic acid solution, sodium gluconate solution, ethylenediaminetetraacetic acid solution, sodium ethylenediaminetetraacetate solution, and ammonia water; more preferably, the complexing agent solution is ammonia water.
[0014] Preferably, the concentration of the complexing agent solution is 4-10 mol / L.
[0015] Preferably, the first antioxidant solution is any one or more of ascorbic acid (vitamin C), sodium citrate, and citric acid; more preferably, the selected first antioxidant is ascorbic acid (vitamin C).
[0016] Preferably, the concentration of the first antioxidant solution is 0.15-0.5 g / L.
[0017] Preferably, the reactor bottom liquid is prepared from water, a second oxidant, a precipitant and a complexing agent.
[0018] Preferably, the temperature of the bottom liquid of the reactor is 40-60°C, the pH value is 11-12, and the alkalinity C(NH4 + ) is 3.0~9.0g / L.
[0019] Preferably, the second antioxidant solution is any one or more of hydrazine hydrate solution, hydrazine solution, and carbohydrazide solution; more preferably, the selected second antioxidant is hydrazine hydrate solution.
[0020] Preferably, the concentration of the second antioxidant solution in the reactor bottom liquid is 0.3-0.8 g / L.
[0021] Preferably, in step 2 and step 3, the alkalinity in the reaction system is 5-8 g / L.
[0022] Preferably, in step 2 and step 3, the temperature of the reaction system is 40-60°C; more preferably, the temperature of the reaction system is 50°C.
[0023] Preferably, the first stage in step 2 is reacted for 28 to 32 hours or the D50 of the precipitated particles is 2.0 to 2.5 μm before entering the second stage; the second stage in step 2 is reacted for 15 to 20 hours or the D50 of the precipitated particles is 3.0 to 3.5 μm before entering step 3.
[0024] Preferably, in step 3, the reaction time is 8-12 hours or the D50 of the precipitated particles is 3.7-5 μm before proceeding to step 4.
[0025] Preferably, in step 2, the flow rate of the metal salt mixed solution A is 30% to 90% of the flow rate of the metal salt mixed solution B in step 3.
[0026] More preferably, in step 2, the flow rate of the metal salt mixed solution A is 80-360 mL / min; in step 3, the flow rate of the metal salt mixed solution B is 180-420 mL / min.
[0027] Preferably, the inert gas providing the inert atmosphere is any one or more of nitrogen, argon and neon.
[0028] Preferably, in step 3, the method further comprises: aging the slurry obtained in step 3 at room temperature for 0.5 to 1 h.
[0029] Preferably, in step 4, during drying, the washed precursor particles are first dried at 70-90° C. for 3-5 hours, and then heated to 110-140° C. for drying for 10-16 hours.
[0030] In a third aspect, the present invention provides a positive electrode material, wherein the raw material of the positive electrode material includes the above-mentioned sodium ion battery quaternary precursor or the sodium ion battery quaternary precursor prepared by the above-mentioned preparation method.
[0031] In a fourth aspect, the present invention provides a battery comprising the above-mentioned positive electrode material.
[0032] Compared with the prior art, the present invention has the following obvious beneficial effects: (1) The preparation method of the present invention can prepare a quaternary sodium electrode precursor comprising orderly intercalated flaky primary particles, uniform pore distribution, and good secondary particle sphericity. The precursor has a dense structure, a high tap density, and good product consistency. The preparation method of the present invention is simple, has strong applicability, requires relatively simple equipment, is easy to operate, and has low control difficulty.
[0033] (2) The present invention uses a two-stage method to prepare a "core-shell" structure precursor to obtain a core with high tap density and good morphology, and then coats the core surface with a doped metal by adjusting the process conditions. By adjusting the two-stage process parameters, the deposition rate of the doped metal is further adjusted to prevent element segregation. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the precursor prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the precursor prepared in Example 4 of the present invention; Figure 3 This is a SEM image of the precursor prepared in Comparative Example 1 of the present invention; Figure 4 This is a SEM image of the precursor prepared in Comparative Example 2 of the present invention; Figure 5 This is the SME diagram of the precursor prepared in Comparative Example 3 of the present invention; Figure 6 This is a SEM image of the precursor prepared in Comparative Example 4 of the present invention; Figure 7 This is a SEM image of the precursor prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0035] The present invention provides the following specific technical solutions.
[0036] In a first aspect, the present invention provides a sodium ion battery quaternary precursor, comprising a core and a shell layer covering at least a portion of the surface of the core; the chemical formula of the core is Ni x1 Zn y1 Fe z1 Mn 1-x1-y1-z1 (OH)2, wherein 0.1≤x1≤0.4, 0≤y1≤0.03, 0.1≤z1≤0.5, x1+y1+z1<1; the chemical formula of the shell is Ni x2 Zn y2 Fe z2 Mn 1-x2-y21-z2 (OH)2, wherein 0.1≤x2≤0.4, 0.04≤y2≤0.12, 0.1≤z2≤0.5, x2+y2+z2<1; the tap density of the sodium ion battery quaternary precursor is 1.4~1.8g / cm 3 .
[0037] Preferably, the primary particles of the sodium ion battery quaternary precursor are in the form of ordered intercalated sheets; and the secondary particles of the sodium ion battery quaternary precursor are in the form of spheres or quasi-spheres.
[0038] In a second aspect, the present invention provides a method for preparing a quaternary precursor for a sodium ion battery, comprising the following steps: Step 1, mixing nickel salt, iron salt, manganese salt, zinc salt and a first antioxidant solution to obtain a metal salt mixed solution A; mixing nickel salt, iron salt, manganese salt, zinc salt and a first antioxidant solution to obtain a metal salt mixed solution B; wherein the zinc salt concentration in the metal salt mixed solution B is higher than the zinc salt concentration in solution A; Step 2, continuously introducing metal salt mixed solution A, precipitant solution and complexing agent solution into the bottom liquid of the reaction kettle under an inert atmosphere to prepare the core, wherein the preparation of the core includes a first stage and a second stage, and the pH value in the reaction system in the first stage is 0.5-1.0 higher than the pH value in the reaction system in the second stage; in the first stage, the pH value of the reaction system is adjusted to 11.0-12.0, and after a certain reaction time, the second stage is entered, and then the pH value of the reaction system is adjusted to 10.5-11.0, and the reaction time is a certain time; Step 3, stop introducing the metal salt mixed solution A, continue to introduce the metal salt mixed solution B, the precipitant solution and the complexing agent solution into the bottom liquid of the reactor, adjust the pH value of the reaction system to 9-10, react for a certain time, and obtain a slurry; Step 4, solid-liquid separation of the slurry obtained in step 3, and then solid-liquid separation, washing, and drying to obtain the sodium ion battery quaternary precursor material.
[0039] It should be noted that the molar ratio of nickel, zinc, iron and manganese in the metal salt mixed solution A is consistent with the stoichiometric ratio of each element in the precursor core; the molar ratio of nickel, zinc, iron and manganese in the metal salt mixed solution B is consistent with the stoichiometric ratio of each element in the precursor shell. In practical applications, precursors with different element ratios can be obtained by adjusting the ratio of salt A and salt B. For example, the core can be Ni 0.1 Zn 0.03 Fe 0.3 Mn 0.57 (OH)2、Ni 0.2 Zn 0.02 Fe 0.1 Mn 0.68 (OH)2、Ni 0.3 Zn 0.03 Fe 0.4 Mn 0.27 (OH)2、Ni 0.4 Zn 0.02 Fe 0.4 Mn 0.18 (OH)2、Ni 0.4 Fe 0.5 Mn 0.1 (OH)2; the shell can be Ni 0.1 Zn 0.1 Fe 0.5 Mn 0.3 (OH)2、Ni 0.2 Zn 0.04 Fe 0.4 Mn 0.36 (OH)2、Ni 0.3 Zn 0.08 Fe 0.3 Mn 0.32 (OH)2、Ni 0.4 Zn 0.12 Fe 0.1 Mn 0.38 (OH)2; and in a specific embodiment of the present invention, in order to reduce the effect of the doping amount of zinc element on the morphology and tap density, the zinc content in the precursor samples prepared in the control example and the comparative example is consistent.
[0040] The inventors found that when zinc is doped by the coprecipitation process, if the content of zinc is high, zinc hydroxide is easily precipitated alone, resulting in a low tap density of the secondary particles of the obtained precursor, thin primary particles, and poor sphericity. To solve the above problems, a higher pH value in step 2 (nucleation stage) is conducive to the precipitation and nucleation of metal elements, and a low pH in step 3 (coating stage) is conducive to the rapid precipitation and growth of metal elements. The pH value of the nucleation stage is adjusted in stages in step 2, which is conducive to the coprecipitation of zinc and other elements and reduces the possibility of precipitation of zinc alone.
[0041] A further preferred solution is: doping a small amount of zinc into the core can reduce the content of zinc in the shell, make the zinc precipitation of the shell more uniform, reduce the possibility of segregation when doping zinc, increase the tap density of the precursor and optimize the morphology characteristics.
[0042] Preferably, the nickel salt, iron salt, manganese salt and zinc salt are each independently any one or more of sulfate, nitrate, acetate and chlorate.
[0043] Preferably, the precipitant solution is any one or more of a sodium hydroxide solution and a potassium hydroxide solution; more preferably, the precipitant solution is a sodium hydroxide solution.
[0044] Preferably, the concentration of the precipitant solution is 8-12 mol / L.
[0045] Preferably, the complexing agent solution is any one or more of sodium citrate solution, sodium fluoride solution, hydroxyethylethylenediaminetriacetic acid solution, sodium gluconate solution, ethylenediaminetetraacetic acid solution, sodium ethylenediaminetetraacetate solution, and ammonia water; more preferably, the complexing agent solution is ammonia water.
[0046] Preferably, the concentration of the complexing agent solution is 4-10 mol / L.
[0047] Preferably, the first antioxidant solution is any one or more of ascorbic acid (vitamin C), sodium citrate, and citric acid; more preferably, the selected first antioxidant is ascorbic acid (vitamin C).
[0048] Preferably, the concentration of the first antioxidant solution is 0.15-0.5 g / L.
[0049] Preferably, the reactor bottom liquid is prepared from water, a second oxidant, a precipitant and a complexing agent.
[0050] By adding the first antioxidant and the second antioxidant, the oxidation of ferrous ions and divalent manganese ions in the metal salt solution can be avoided, thereby preventing the oxidation of ferrous ions and divalent manganese ions from causing precipitation segregation, making the particle growth trend worse, changing the morphology, and affecting the overall precipitation effect. The second antioxidant exhibits strong reducing properties under alkaline conditions, which can effectively prevent the oxidation of ferrous ions and divalent manganese ions, and further ensure the stability in the initial stage of the reaction.
[0051] Preferably, the temperature of the bottom liquid of the reactor is 40-60°C, the pH value is 11-12, and the alkalinity C(NH4 + ) is 3.0~9.0g / L.
[0052] By setting the bottom liquid of the reactor, the fluctuation of the reaction conditions can be controlled and the impact of the fluctuation of the reaction conditions on the reaction can be reduced. If the deviation between the bottom liquid conditions and the reaction conditions is too large, it may cause adverse effects such as particle agglomeration or incomplete precipitation in the early stage of the reaction.
[0053] Preferably, the second antioxidant solution is any one or more of hydrazine hydrate solution, hydrazine solution, and carbohydrazide solution; more preferably, the selected second antioxidant is hydrazine hydrate solution.
[0054] Preferably, the concentration of the second antioxidant solution in the reactor bottom liquid is 0.3-0.8 g / L.
[0055] Preferably, in step 2 and step 3, the alkalinity in the reaction system is 5-8 g / L.
[0056] Preferably, in step 2 and step 3, the temperature of the reaction system is 40-60°C.
[0057] In practical applications, the temperature of the reaction system can be 40°C, 45°C, 50°C, 55°C, or 60°C.
[0058] Preferably, the first stage in step 2 is reacted for 28 to 32 hours or the D50 of the precipitated particles is 2.0 to 2.5 μm before entering the second stage; the second stage in step 2 is reacted for 15 to 20 hours or the D50 of the precipitated particles is 3.0 to 3.5 μm before entering step 3.
[0059] Preferably, in step 3, the reaction time is 8-12 hours or the D50 of the precipitated particles is 3.7-5 μm before proceeding to step 4.
[0060] Preferably, in step 2, the flow rate of the metal salt mixed solution A is 30% to 90% of the flow rate of the metal salt mixed solution B in step 3.
[0061] The flow rate in step 3 is greater than the flow rate in step 2, and setting the flow rate in a gradient is beneficial to accelerating the growth of particle size.
[0062] More preferably, in step 2, the flow rate of the metal salt mixed solution A is 80-360 mL / min; in step 3, the flow rate of the metal salt mixed solution B is 180-420 mL / min.
[0063] Preferably, the inert gas providing the inert atmosphere is any one or more of nitrogen, argon and neon.
[0064] Preferably, in step 3, the method further comprises: aging the slurry obtained in step 3 at room temperature for 0.5 to 1 h.
[0065] Preferably, in step 4, during drying, the washed precursor particles are first dried at 70-90° C. for 3-5 hours, and then heated to 110-140° C. for drying for 10-16 hours.
[0066] In a third aspect, the present invention provides a positive electrode material, wherein the raw material of the positive electrode material includes the above-mentioned sodium ion battery quaternary precursor or the sodium ion battery quaternary precursor prepared by the above-mentioned preparation method.
[0067] In a fourth aspect, the present invention provides a battery comprising the above-mentioned positive electrode material.
[0068] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.
[0069] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0070] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0071] Embodiment 1: A method for preparing a quaternary precursor for a sodium ion battery comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron and manganese in metal salt mixed solution A is 1:1:1, and the total concentration of metal ions is 2 mol / L. Mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.24:0.33:0.33:0.10, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of ascorbic acid in metal salt mixed solution A and metal salt mixed solution B is 0.3 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0072] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0073] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, the flow rate of sodium hydroxide is 50 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours, and the introduction of metal salt mixed solution A is stopped after the reaction is continued for 20 hours; the core of the precursor is obtained, and the general formula is Ni 0.33 Fe 0.33 Mn 0.33 (OH)2.
[0074] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 360 mL / min, the flow rate of ammonia water is adjusted to 60 mL / min, the flow rate of sodium hydroxide solution is 150 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 7.0 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0075] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.33 Fe 0.33 Mn 0.33 (OH)2@Ni 0.24 Zn 0.1 Fe 0.33 Mn 0.33 (OH)2.
[0076] Embodiment 2: A method for preparing a sodium ion battery quaternary precursor comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution, manganese sulfate solution and zinc nitrate solution to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution A is 0.33:0.33:0.33:0.01, and the total concentration of metal ions is 2 mol / L. Mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.24:0.33:0.33:0.10, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of sodium citrate in metal salt mixed solution A and metal salt mixed solution B is 0.15 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0077] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 2000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 5g / L and the pH value was 11.10. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0078] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 80 mL / min, the flow rate of ammonia water is 10 mL / min, the flow rate of sodium hydroxide is 30 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, the alkalinity is 5 g / L, the stirring rate in the reactor is 500 r / min, the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours, and the introduction of metal salt mixed solution A is stopped after the reaction is continued for 20 hours; the core of the precursor is obtained, and the general formula is Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2.
[0079] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 180 mL / min, the flow rate of ammonia water is adjusted to 30 mL / min, the flow rate of sodium hydroxide solution is 75 mL / min, the pH value of the reaction system is controlled to be 9.0-9.5, and the alkalinity is 5 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0080] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2@Ni 0.24 Zn 0.1 Fe 0.33 Mn 0.33 (OH)2.
[0081] Embodiment 3: A method for preparing a sodium ion battery quaternary precursor comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution, manganese sulfate solution and zinc sulfate solution to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution A is 0.31:0.33:0.33:0.03, and the total concentration of metal ions is 2 mol / L. Mixing sulfuric acid solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.26:0.33:0.33:0.08, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of sodium citrate in metal salt mixed solution A and metal salt mixed solution B is 0.5 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0082] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 150mL of NaOH solution and 3500mL of ammonia solution were added into the reactor, the alkalinity of the reactor bottom liquid was adjusted to 8g / L, and the pH value was 11.60. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0083] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 360 mL / min, the flow rate of ammonia water is 60 mL / min, the flow rate of sodium hydroxide is 150 mL / min, the pH value of the reaction system is controlled to be 11.5-12.0, the alkalinity is 8 g / L, the stirring rate in the reactor is 500 r / min, the pH value of the reaction system is controlled to be 10.5-11.0 after reacting for 30 hours, and the introduction of metal salt mixed solution A is stopped after continuing the reaction for 20 hours, so as to obtain the core of the precursor, which has the general formula of Ni 0.31 Zn 0.03 Fe 0.33 Mn 0.33 (OH)2.
[0084] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 420 mL / min, the flow rate of ammonia water is adjusted to 80 mL / min, the flow rate of sodium hydroxide solution is 180 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 8 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0085] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.31 Zn 0.03 Fe 0.33 Mn 0.33 (OH)2@Ni 0.26 Zn 0.08 Fe 0.33 Mn 0.33 (OH)2.
[0086] Embodiment 4: A method for preparing a quaternary precursor for a sodium ion battery comprises the following steps: Step 1, mix nickel sulfate solution, ferrous sulfate solution, manganese sulfate solution and zinc sulfate to prepare metal salt mixed solution A, the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution A is 0.33:0.33:0.33:0.01, and the total metal ion concentration is 2 mol / L. Mix nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.24:0.33:0.33:0.10, and the total metal ion concentration is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of ascorbic acid in metal salt mixed solution A and metal salt mixed solution B is 0.3 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0087] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, the flow rate of sodium hydroxide is 50 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours. After continuing the reaction for 20 hours, stop introducing the metal salt mixed solution A, and obtain the core of the precursor, which has the general formula of Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2.
[0088] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 270 mL / min, the flow rate of ammonia water is adjusted to 45 mL / min, the flow rate of sodium hydroxide solution is 120 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 7 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0089] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2@Ni 0.24 Zn 0.1 Fe 0.33 Mn 0.33 (OH)2.
[0090] Embodiment 5: A method for preparing a sodium ion battery quaternary precursor comprises the following steps: Step 1, mix nickel sulfate solution, ferrous sulfate solution, manganese sulfate solution and zinc sulfate to prepare metal salt mixed solution A, the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution A is 0.32:0.33:0.33:0.02, and the total concentration of metal ions is 2 mol / L. Mix nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.26:0.33:0.33:0.08, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of ascorbic acid in metal salt mixed solution A and metal salt mixed solution B is 0.3 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0091] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, the flow rate of sodium hydroxide is 50 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours. After continuing the reaction for 20 hours, stop introducing the metal salt mixed solution A, and obtain the core of the precursor, which has the general formula of Ni 0.32 Zn 0.02 Fe 0.33 Mn 0.33 (OH)2.
[0092] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 270 mL / min, the flow rate of ammonia water is adjusted to 45 mL / min, the flow rate of sodium hydroxide solution is 120 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 7 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0093] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.32 Zn 0.02 Fe 0.33 Mn 0.33 (OH)2@Ni 0.26 Zn 0.08 Fe 0.33 Mn 0.33 (OH)2.
[0094] Comparative Example 1: A method for preparing a quaternary precursor for a sodium ion battery comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron and manganese in metal salt mixed solution A is 1:1:1, and the total concentration of metal ions is 2 mol / L. Mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.24:0.33:0.33:0.10, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of ascorbic acid in metal salt mixed solution A and metal salt mixed solution B is 0.3 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0095] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0096] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, and the flow rate of sodium hydroxide is 50 mL / min, and the pH value of the reaction system is controlled to be 11.0-11.5 and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the introduction of metal salt mixed solution A is stopped after the reaction for 50 hours, so as to obtain the core of the precursor, which has the general formula of Ni 0.33 Fe0.33 Mn 0.33 (OH)2.
[0097] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 360 mL / min, the flow rate of ammonia water is adjusted to 60 mL / min, the flow rate of sodium hydroxide solution is 150 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 7.0 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0098] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.33 Fe 0.33 Mn 0.33 (OH)2@Ni 0.24 Zn 0.1 Fe 0.33 Mn 0.33 (OH)2.
[0099] Comparative Example 2: A method for preparing a sodium ion battery quaternary precursor comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution, zinc sulfate solution and manganese sulfate solution to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution A is 0.33:0.33:0.33:0.01, and the total concentration of metal ions is 2 mol / L. Mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.24:0.33:0.33:0.10, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of ascorbic acid in metal salt mixed solution A and metal salt mixed solution B is 0.3 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0100] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0101] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, the flow rate of sodium hydroxide is 50 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours. After continuing the reaction for 20 hours, stop introducing the metal salt mixed solution A, and obtain the core of the precursor, which has the general formula of Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2.
[0102] Step 4: introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 270 mL / min, the flow rate of ammonia water is adjusted to 45 mL / min, the flow rate of sodium hydroxide solution is 120 mL / min, and the pH value of the reaction system is maintained at 10.5-11.0 and the alkalinity is 7 g / L. After 11 hours of reaction, when the D50 of the precipitated particles is 3.7-5 μm, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0103] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2@Ni 0.24 Zn 0.1 Fe 0.33 Mn 0.33 (OH)2.
[0104] Comparative Example 3: A method for preparing a quaternary precursor for a sodium ion battery comprises the following steps: Step 1, mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in the metal salt mixed solution B is 0.30:0.33:0.33:0.04, and the total concentration of metal ions is 2 mol / L. Ascorbic acid is added to the two metal salt solutions, and the concentration of ascorbic acid in the metal salt mixed solution B is 0.3 g / L. 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution are prepared.
[0105] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0106] Step 3: continuously introduce metal salt mixed solution B into the bottom liquid of the reactor, the flow rate of metal salt mixed solution B is 120 mL / min, the flow rate of ammonia water is adjusted to 20 mL / min, the flow rate of sodium hydroxide solution is 50 mL / min, the pH value of the reaction system is controlled to be 10.5-11.5, and the alkalinity is 7 g / L. After 83 hours of reaction, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0107] Step 4, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor Ni 0.30 Zn 0.04 Fe 0.33 Mn 0.33 (OH)2.
[0108] Comparative Example 4: A method for preparing a quaternary precursor for a sodium ion battery comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution, manganese sulfate solution and zinc sulfate to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution A is 0.30:0.32:0.32:0.06, and the total concentration of metal ions is 2 mol / L. Mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in metal salt mixed solution B is 0.30:0.34:0.34:0.02, and the total concentration of metal ions is 2 mol / L. Add ascorbic acid to the two metal salt solutions, and the concentration of ascorbic acid in metal salt mixed solution A and metal salt mixed solution B is 0.3 g / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0109] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 300mL of 25% mass concentration of hydrazine hydrate, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor.
[0110] Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, the flow rate of sodium hydroxide is 50 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours. After continuing the reaction for 20 hours, stop introducing the metal salt mixed solution A, and obtain the core of the precursor, which has the general formula of Ni 0.30 Zn 0.06 Fe 0.32 Mn 0.32 (OH)2.
[0111] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 360 mL / min, the flow rate of ammonia water is adjusted to 60 mL / min, the flow rate of sodium hydroxide solution is 150 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 7 g / L. After reacting for 17 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0112] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.30 Zn 0.06 Fe 0.32 Mn 0.32 (OH)2@Ni 0.3 Zn 0.02 Fe 0.34 Mn 0.34 (OH)2.
[0113] Comparative Example 5: A method for preparing a sodium ion battery quaternary precursor comprises the following steps: Step 1, mixing nickel sulfate solution, ferrous sulfate solution, manganese sulfate solution and zinc sulfate to prepare metal salt mixed solution A, wherein the molar ratio of nickel, iron, manganese and zinc in the metal salt mixed solution A is 0.33:0.33:0.33:0.01, and the total metal ion concentration is 2 mol / L. Mixing nickel sulfate solution, zinc sulfate solution, ferrous sulfate solution and manganese sulfate solution to prepare metal salt mixed solution B, wherein the molar ratio of nickel, iron, manganese and zinc in the metal salt mixed solution B is 0.24:0.33:0.33:0.10, and the total metal ion concentration is 2 mol / L. Prepare 6.7 mol / L ammonia water and 10.8 mol / L sodium hydroxide solution.
[0114] Step 2, preparation of reaction bottom liquid: 200L of pure water was introduced into a 300L reactor, the temperature was raised to 50°C, 120mL of NaOH solution and 3000mL of ammonia solution were added into the reactor, and the alkalinity of the reactor bottom liquid was adjusted to 7.0g / L and the pH value was 11.40. Then N2 was introduced into the reactor at a flow rate of 20L / h for 1h to replace the air in the reactor; Step 3: continuously introduce metal salt mixed solution A, ammonia water and sodium hydroxide solution into the bottom liquid of the reactor, the flow rate of metal salt mixed solution A is 120 mL / min, the flow rate of ammonia water is 20 mL / min, the flow rate of sodium hydroxide is 50 mL / min, the pH value of the reaction system is controlled to be 11.0-11.5, and the alkalinity is 7 g / L; the stirring rate in the reactor is 500 r / min, and the pH value of the reaction system is controlled to be 10.5-11.0 after the reaction for 30 hours. After continuing the reaction for 20 hours, stop introducing the metal salt mixed solution A, and obtain the core of the precursor, which has the general formula of Ni 0.33 Zn 0.01 Fe 0.33 Mn0.33 (OH)2.
[0115] Step 4, introducing metal salt mixed solution B into the reaction system, the flow rate of metal salt mixed solution B is 270 mL / min, the flow rate of ammonia water is adjusted to 45 mL / min, the flow rate of sodium hydroxide solution is 120 mL / min, the pH value of the reaction system is controlled to be 9.5-10.0, and the alkalinity is 7 g / L. After reacting for 11 hours, stop introducing metal salt mixed solution B, ammonia water and sodium hydroxide solution.
[0116] Step 5, aging, adding 150L of 5% sodium hydroxide solution to the reactor for aging for 0.5h, then filtering the aged slurry, and repeatedly washing the filtered solid particles with pure water. When the pH value of the deionized water after washing is less than 8.0, the washing can be stopped; then the solid particles are dried at 80°C for 4h and then heated to 120°C for 14h to obtain the precursor, which has the general formula Ni 0.33 Zn 0.01 Fe 0.33 Mn 0.33 (OH)2@Ni 0.24 Zn 0.1 Fe 0.33 Mn 0.33 (OH)2.
[0117] The precursors prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were sampled and tested. The element content of the precursors was tested by ICP, the tap density of the precursors was tested by a tap density meter, and the D50 of the precursors was tested by a laser particle size analyzer. The test results are shown in Table 1 below.
[0118] Table 1 Element content, D50 and tap density of sodium ion battery quaternary precursors prepared in Examples 1 to 5 and Comparative Examples 1 to 5 Comparing the tap density of the precursors prepared in Example 1 and Example 4, the tap density of the precursor prepared in Example 4 is higher. The inventors speculate that doping the core with a small amount of zinc element can reduce the zinc content in the shell layer, make the zinc element precipitation in the shell layer more uniform, reduce the possibility of its single precipitation, and improve the tap density.
[0119] By comparing the tap density of the precursors prepared in Example 1 and Comparative Example 1, it can be seen that the density of the precursor prepared in Example 1 is high, which can prove that adjusting the pH value in stages when precipitating nuclei is beneficial to the co-precipitation of zinc and other elements, avoiding the precipitation of zinc alone, thereby improving the tap density of the precursor.
[0120] Comparing Example 4 with Example 2, the tap density of the precursor prepared in Example 4 is higher. The inventors speculate that the pH value of the first stage precipitation being higher than the pH value of the second stage precipitation is conducive to the complete precipitation of zinc hydroxide, making the structure more compact, which is conducive to the improvement of the tap density.
[0121] By comparing the tap density of the precursors obtained in Example 4 and Comparative Example 3, it can be seen that the tap density of the precursor obtained in Example 4 is higher, and zinc element is difficult to co-precipitate with other metal elements. Direct co-precipitation is likely to cause zinc hydroxide to precipitate alone, thereby affecting the tap density of the precursor.
[0122] Comparing the tap density of the precursors prepared in Example 4 and Comparative Example 4, the tap density of the precursor prepared in Example 4 is higher. The inventors speculate that the zinc content concentration in the core is lower than the zinc content concentration in the coating layer, which can increase the tap density. Too high zinc content in the core will cause zinc hydroxide to precipitate alone, resulting in a loose core structure and a decrease in the tap density.
[0123] Comparative Example 4 and Comparative Example 5, not adding an antioxidant will result in the sample being oxidized to a certain extent during the preparation process, the primary particles becoming thinner, and the tap density decreasing.
[0124] Figure 1 This is a SEM image of the precursor prepared in Example 1 of the present invention. Figure 1 It can be seen that the primary particles of the precursor are uniform intercalated thick flakes, the secondary particles have good sphericity, the particles are relatively dense, and there is no agglomeration phenomenon.
[0125] Figure 2 This is a SEM image of the precursor obtained in Example 4 of the present invention. Figure 2 It can be seen that the primary particles of the precursor present uniform intercalated thick flakes, the secondary particles have good sphericity, the particles are relatively dense, and there is no agglomeration phenomenon.
[0126] contrast Figure 1 and Figure 2 It can be seen that the overall primary particles of the precursor prepared in Example 4 are denser and have better sphericity, indicating that doping a small amount of zinc in the core is more conducive to improving the co-precipitation of zinc and other elements in the precursor. Combined with the data in Table 1, it can be further proved that doping zinc in the core is beneficial to improving the morphology and tap density of the precursor.
[0127] Figure 3 is the SEM image of the precursor prepared in Comparative Example 1. Figure 3 It can be seen that the primary particles of the precursor are uniform intercalated thick sheets, there are flocculent structures on the surface of the primary particles, and the secondary particles are spherical without agglomeration.
[0128] Will Figure 3 and Figure 1 , Figure 2 By comparison, it can be seen that the spherical shape of the precursor prepared in comparative example 1 is relatively loose when observed with the naked eye, which further proves that doping a small amount of zinc element in the core is beneficial to improving the morphology and tap density of the precursor.
[0129] Figure 4 is the SEM image of the precursor obtained in Comparative Example 2. Figure 4 It can be seen that the primary particles of the precursor prepared in Comparative Example 2 are thick intercalated flakes, and the sphericity of the secondary particles is poor.
[0130] The inventors speculate that the reason for the poor morphology and tap density of the precursor in Comparative Example 2 may be that the pH value in the "shell-core" stage was not adjusted, which affected the morphology and tap density of the precursor.
[0131] Figure 5 This is the SEM image of the precursor obtained in Comparative Example 3. Figure 5 It can be seen that the primary particles of the precursor prepared in Comparative Example 3 are in the shape of inserts, but the overall sphericity and density of the secondary particles are poor.
[0132] contrast Figure 2 and Figure 5 It is further proved that the process of preparing the core-shell structure in stages provided by the present invention can optimize the morphology of the precursor, reduce the possibility of zinc element precipitation alone, make the overall structure of the precursor more compact, the primary particle flakes more obvious, and improve the sphericity of the precursor.
[0133] Figure 6 is the SEM image of the precursor prepared in Comparative Example 4. Figure 6 It can be seen that the primary particles of the precursor prepared in Comparative Example 4 are thick intercalated flakes, and the secondary particles have poor sphericity and density.
[0134] contrast Figure 2 and Figure 6 The inventors speculate that the reason for the poor morphology and tap density of the precursor of Comparative Example 4 may be that the content of zinc doped in the core is too high, and the excessive zinc element precipitates alone, affecting the sphericity and density of the precursor.
[0135] Figure 7 is the SEM image of the precursor prepared in Comparative Example 5. Figure 7 It can be seen that the primary particles of the precursor are layered structures, and the layered structures are relatively thin, without agglomeration. The inventors speculate that the reason for this morphology is that the absence of antioxidants will cause the sample to be oxidized to a certain extent during the preparation process, the primary particles become thinner, and the tap density decreases.
[0136] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A sodium ion battery quaternary precursor, characterized in that: It comprises a core and a shell layer covering at least a portion of the surface of the core; the chemical formula of the core is Ni x1 Zn y1 Fe z1 Mn 1-x1-y1-z1 (OH)2, wherein 0.1≤x1≤0.4, 0≤y1≤0.03, 0.1≤z1≤0.5, x1+y1+z1<1; the chemical formula of the shell is Ni x2 Zn y2 Fe z2 Mn 1-x2-y21-z2 (OH)2, wherein 0.1≤x2≤0.4, 0.04≤y2≤0.12, 0.1≤z2≤0.5, x2+y2+z2<1; the tap density of the sodium ion battery quaternary precursor is 1.4~1.8g / cm 3 .
2. The sodium ion battery quaternary precursor according to claim 1, characterized in that: The primary particles of the sodium ion battery quaternary precursor are in the form of ordered intercalated sheets; the secondary particles of the sodium ion battery quaternary precursor are in the form of spheres or quasi-spheres.
3. A method for preparing a sodium ion battery quaternary precursor according to any one of claims 1 to 2, characterized in that: The steps include: Step 1, mixing nickel salt, iron salt, manganese salt, zinc salt and a first antioxidant solution to obtain a metal salt mixed solution A; mixing nickel salt, iron salt, manganese salt, zinc salt and a first antioxidant solution to obtain a metal salt mixed solution B; wherein the zinc salt concentration in the metal salt mixed solution B is higher than the zinc salt concentration in solution A; Step 2, continuously introducing metal salt mixed solution A, precipitant solution and complexing agent solution into the bottom liquid of the reaction kettle under an inert atmosphere to prepare the core, wherein the preparation of the core includes a first stage and a second stage, and the pH value in the reaction system in the first stage is 0.5-1.0 higher than the pH value in the reaction system in the second stage; in the first stage, the pH value of the reaction system is adjusted to 11.0-12.0, and after a certain reaction time, the second stage is entered, and then the pH value of the reaction system is adjusted to 10.5-11.0, and the reaction time is a certain time; Step 3, stop introducing the metal salt mixed solution A, continue to introduce the metal salt mixed solution B, the precipitant solution and the complexing agent solution into the bottom liquid of the reactor, adjust the pH value of the reaction system to 9-10, react for a certain time, and obtain a slurry; Step 4, solid-liquid separation of the slurry obtained in step 3, and then solid-liquid separation, washing, and drying to obtain the sodium ion battery quaternary precursor material.
4. A method for preparing a quaternary precursor for a sodium ion battery as claimed in claim 3, characterized in that: After the first stage of step 2 reacts for 28 to 32 hours or the D50 of the precipitated particles is 2.0 to 2.5 μm, the second stage is entered; after the second stage of step 2 reacts for 15 to 20 hours or the D50 of the precipitated particles is 3.0 to 3.5 μm, the step is entered into step 3; in step 3, the reaction time is 8 to 12 hours or the D50 of the precipitated particles is 3.7 to 5 μm, the step is entered into step 4.
5. A method for preparing a quaternary precursor for a sodium ion battery as claimed in claim 3, characterized in that: In step 2, the flow rate of the metal salt mixed solution A is 30% to 90% of the flow rate of the metal salt mixed solution B in step 3; the flow rate of the metal salt mixed solution A is 80 to 360 mL / min; in step 3, the flow rate of the metal salt mixed solution B is 180 to 420 mL / min.
6. A method for preparing a sodium ion battery quaternary precursor as claimed in claim 3, characterized in that: The nickel salt, iron salt, manganese salt and zinc salt are each independently any one or two or more of sulfate, nitrate, acetate and chlorate; The precipitant solution is any one or more of a sodium hydroxide solution and a potassium hydroxide solution; the concentration of the precipitant solution is 8-12 mol / L; The complexing agent solution is any one or more of sodium citrate solution, sodium fluoride solution, hydroxyethylethylenediaminetriacetic acid solution, sodium gluconate solution, ethylenediaminetetraacetic acid solution, sodium ethylenediaminetetraacetate solution, and ammonia water; the concentration of the complexing agent solution is 4-10 mol / L; The first antioxidant solution is any one or more of ascorbic acid, sodium citrate, and citric acid; the concentration of the first antioxidant solution is 0.15-0.5 g / L; In step 2 and step 3, the alkalinity in the reaction system is 5-8 g / L.
7. A method for preparing a sodium ion battery quaternary precursor as claimed in claim 3, characterized in that: The reactor bottom liquid is prepared from water, a second oxidant, a precipitant and a complexing agent; the second antioxidant solution is any one or more of a hydrazine hydrate solution, a hydrazine solution and a carbohydrazide solution; and the concentration of the second antioxidant in the reactor bottom liquid is 0.3-0.8 g / L.
8. A method for preparing a sodium ion battery quaternary precursor as claimed in claim 7, characterized in that: The temperature of the bottom liquid of the reaction kettle is 40-60° C., the pH value is 11-12, and the alkalinity is 3.0-9.0 g / L.
9. A positive electrode material, characterized in that: The raw material of the positive electrode material includes the sodium ion battery quaternary precursor according to any one of claims 1 to 2 or the sodium ion battery quaternary precursor prepared by the preparation method according to any one of claims 3 to 8.
10. A battery, characterized in that: Comprising the positive electrode material according to claim 9.
Citation Information
Patent Citations
Nickel-iron-manganese-based sodium-ion battery precursor as well as preparation method and application thereof
CN116639737A
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN117117144A
Zinc-doped sodium ion battery positive electrode material precursor and preparation method thereof
CN117401726A
Layered oxide positive electrode material, preparation method and application thereof
CN117712317A
Iron-based precursor material and preparation method and application thereof
CN118005100A